Documentation IZAΨMOD v3.0: The IZA Policy Simulation Model - Max Loeffler; Andreas Peichl; Nico Pestel; Sebastian Siegloch; Eric Sommer (Institute for the Study of Labor (IZA), 2014)
This paper describes IZAΨMOD, the policy microsimulation model of the Institute for the Study of Labor (IZA). The model uses household microdata from the German Socio-Economic Panel Study and firm data from the German linked employer-employee dataset LIAB. IZAΨMOD consists of three components: First, a static module simulates the effects of a tax-benefit reform on the budget of the individual household. This includes taxes on income and consumption, social security contributions, public transfers. Secondly, behavioral labor supply responses are estimated. The third component distinguishes our model from most other microsimulation tools. A demand module takes into account possible restrictions of labor demand and identifies the partial equilibrium of the labor market after the supply reactions.
Keywords: D58; H20; J22; J23; 330; microsimulation; tax and benefit systems; labor supply; labor demand; Germany